G × E Interaction and stability analysis to identify resistant mungbean (Vigna radiata L.) genotypes against Boeremia leaf spot using AMMI and GGE biplot analysis - Uzma Rashid; Mohammad Irfan; Mohd Ashraf Bhat; Mohammad Najeeb Mughal; Sajad Un Nabi; Abdel-Halim I. Ghazy; Abdullah A. Al-Doss (BMC Plant Biology)
Abstract Boeremia Leaf Spot (BLS), caused by Boeremia exigua, threatens mungbean cultivation worldwide, exacerbated by its wide host range, multiple pathogenic strains, and environmental influences. A thorough understanding of the host-pathogen-environment interactions is critical for effective disease management. To identify mungbean genotypes resistant to BLS, we conducted multi-environment trials. Initially, 70 genotypes were screened under controlled conditions, and 10 were selected for field trials across four environments over three years. GGE biplot analysis revealed the importance of considering both genetic and environmental factors when evaluating resistance. Based on average disease severity (DS) scores across locations and years, two genotypes, (G5) AG-11 (DS = 4.1) and G7 (AK-58) (DS = 3.4), which demonstrated consistent resistance to BLS across multiple test environments. These genotypes not only exhibited strong disease resistance but also showed stable adaptation both in case of disease resistance and yield output [ (G5) AG-11 (Y = 9.02qtls/ha) and (G7) (AK-58) (y = 12.15 qtls/ha) and therefore were identified as promising resistant candidates. The Additive Main Effects and Multiplicative Interaction (AMMI) model, in conjunction with the GGE biplot, effectively analyzed genotype-environment interactions and identified optimal evaluation sites and “mega-environments” for BLS resistance. These findings provide valuable insights for future breeding programs focused on integrating resistance traits into new mungbean varieties.